Imaging in the Diagnosis of Nonspecific Pyogenic Spondylodiskitis - Heyde, Christoph Eckhard; Spiegl, Ulrich Josef Albert; Voelker, Anna; von der Hoeh, Nicolas; Henkelmann, Jeanette (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
The prevalence of nonspecific pyogenic spondylodiskitis, associated with both a high morbidity and a high mortality, has increased in the last few decades. The diagnosis is often delayed because of the nonspecific clinical manifestation at the early stage. The reliability of radiographs is limited, particularly in early stage after the onset of infection. Computed tomography (CT) can reliably assess the bony condition with the possibility of spatial visualization. Contrast enhancement supports the detection of affected soft tissue. Magnetic resonance imaging (MRI) continues to be the gold standard in the diagnosis of spondylodiskitis. Sophisticated investigation protocols supported by gadolinium enhancement secure the diagnosis. MRI has a high resolution without radiation exposure. Different nuclear investigation techniques extend the diagnostic options. Reports of 18F-fluorodeoxyglucose-positron emission tomography (18-FDG-PET) are particularly promising to confirm the diagnosis. The drawback of the reduced image quality with respect to detailed anatomical information can be overcome by a combined simultaneous acquisition of CT or MRI. With respect to one of the greatest challenges, the differentiation between degenerative changes (Modic type 1) and infection at an early stage using differentiated MRI protocols and FDG-PET is promising. This overview presents a concise state-of-the-art look at radiologic investigations in case of suspected nonspecific pyogenic spondylodiskitis with the focus on a pragmatic approach.
Keywords: spondylodiskitis; spinal infection; radiologic investigation